To Ada or not To Ada: Adaing vs. Javaing in real-time systems - Pinho, Luís Miguel (2014)
Ada is really an unfortunate Lady. After years fighting against C/C++ villains, her major lift-up (Ada 95) had brought up a promise of fortune. However, a new strong villain (Java) has appeared trying to end her struggle for survival. Ada has now to fight with her own weapons. She will only prosper by her own merits. But two questions emerge. Do they exist? Are they better than Java’s? Our opinion is that they do exist, and are not matched by any other programming language